2021
DOI: 10.3892/ol.2021.12852
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑4491 enhances cell proliferation and inhibits cell apoptosis in non‑small cell lung cancer via targeting TRIM7

Abstract: MicroRNAs (miRNAs) are involved in the development of non-small cell lung cancer (NSCLC). However, the biological roles of several aberrantly expressed miRNAs have not been explored yet. In the present study, miR-4491 was identified as a novel upregulated miRNA in NSCLC tissues and cell lines. Downregulation of miR-4491 by a miR-4491 inhibitor inhibited the proliferation and triggered the apoptosis of NSCLC cells. Tripartite motif containing 7 (TRIM7), a tumor suppressor gene expressed in NSCLC, was demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…MiRNAs have been used as markers to predict ovarian cancer sensitivity to platinum and taxane chemotherapeutic agents, which significantly improve treatment outcomes [29]. Some microRNAs are not conducive to cancer outcomes, such as microRNA-4491, which enhances proliferation and inhibits apoptosis in nonsmall cell lung cancer cells [30]. Few studies have assessed the relationship between microRNA-302c and tumors.…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs have been used as markers to predict ovarian cancer sensitivity to platinum and taxane chemotherapeutic agents, which significantly improve treatment outcomes [29]. Some microRNAs are not conducive to cancer outcomes, such as microRNA-4491, which enhances proliferation and inhibits apoptosis in nonsmall cell lung cancer cells [30]. Few studies have assessed the relationship between microRNA-302c and tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Han et al showed that miR-4491 was remarkably upregulated in NSCLC cells. Its overexpression facilitated proliferation and repressed apoptosis in NCI-H1650 cells through targeting TRIM7 (118). LncRNAs and circRNAs can also modulate LC proliferation and apoptosis via serving as ceRNAs for miRNA.…”
Section: Ncrna In Lc Proliferation and Apoptosismentioning
confidence: 99%